2016
DOI: 10.1111/ijlh.12527
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of thalassemia

Abstract: Summary The thalassemias can be defined as α‐ or β‐thalassemias depending on the defective globin chain and on the underlying molecular defects. The recognition of carriers is possible by hematological tests. Both α‐ and β‐thalassemia carriers (heterozygotes) present with microcytic hypochromic parameters with or without mild anemia. Red cell indices and morphology followed by separation and measurement of Hb fractions are the basis for identification of carriers. In addition, iron status should be ascertained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(127 citation statements)
references
References 34 publications
5
113
0
9
Order By: Relevance
“…20 In their study, the Mentzer indices were able to correctly diagnose 94.7% and 92.9% of cases, respectively, and both are easy to calculate. 21 Similar results (Mentzer index: sensitivity, 90.9%; specificity, 80.3%) were found by Ghafouri et al 19 Their results overlapped those of our study. In the present study, YI evaluated the discriminating function of the red cell indices and their derived formulae.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…20 In their study, the Mentzer indices were able to correctly diagnose 94.7% and 92.9% of cases, respectively, and both are easy to calculate. 21 Similar results (Mentzer index: sensitivity, 90.9%; specificity, 80.3%) were found by Ghafouri et al 19 Their results overlapped those of our study. In the present study, YI evaluated the discriminating function of the red cell indices and their derived formulae.…”
Section: Discussionsupporting
confidence: 92%
“…20 Ntaios et al reported a Sn and Sp of 59.78% and 99% respectively with YI of +0.58. 21 Hence Mentzer index showed high validity in this study and these results are comparable to other studies.…”
Section: Discussionsupporting
confidence: 91%
“…There are poor data on the precise prevalence, overall burden, and trends of these diseases in Europe. Although β-thalassemia minor sometimes causes mild anaemia, carriers of disease are usually clinically asymptomatic [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Laboratory diagnosis of thalassemia, which consists of blood film examinations and hemoglobin electrophoresis, are the most common modalities in our country since DNA analysis for  or ß globin mutations is high cost and only available in the capital city. On the other hand, diagnosis of thalassemia becomes more complicated because of high prevalence of iron deficiency anemia in the country [1]. Health survey data in 2001 showed the prevalence of deficiency anemia in infants 0-6 months, infants 6-12 months, and children under five years old were 61.3%, 64.8%, and 48.1%, respectively.…”
Section: Introductionmentioning
confidence: 99%